PENEGAKAN HUKUM OLEH KEPOLISIAN REPUBLIK INDONESIA TERHADAP TINDAK PIDANA TENAGA KERJA ASING ILEGAL (PENELITIAN DI KEPOLISIAN DAERAH SUMATERA UTARA) - Rosmahayati Sitepu (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Law enforcement against immigration crimes, especially the problem of misuse of foreign workers' residence permits by the law enforcement officers, especially Civil Servant investigators is still very weak. The reality shows that of the many cases of misuse of residence permits only a small number have reached the court stage. This can be seen in the development of the issue of illegal foreign workers which is being discussed in the community. The number of foreign workers from China continues to increase and on average these foreign workers do not have and meet the requirements as foreign workers. This situation needs serious attention from the government, especially the law enforcement. Based on the results of the research and discussion, law enforcement by the police is based on the authority of the police as the investigators and conducts the investigations of every criminal act which is regulated in the Criminal Procedure Code and Law no. 2 of 2002 concerning the Police. The obstacle to law enforcement against Illegal Foreign Workers by the Police is the weak authority possessed by the Police; this is related to the handing over of the authority to investigate any criminal act in the field of immigration to the Immigration Civil Servant Investigators. Another obstacle found was the lack of integrated coordination between the immigration civil servants investigators and Republic of Indonesia Police Investigators. Immigration criminal law policies are implemented by formulating immigration criminal offenses and expanding the subject of criminal acts and objects of criminal acts in the field of immigration. In addition, the immigration law criminal policy, namely by qualifying immigration crimes as special crimes, and giving special authority to the Immigration Civil Servant Investigators to conduct investigations on immigration crimes.Keywords: Law Enforcement, Police, Illegal Foreign Workers.